Interrelation Between Religion and Science: An Islamic Philosophical Perspective - Taqiyuddin Kabalmay; Hadi Masruri; Namiyah Fitriani; Ikhwanul Habib; Khasyitullah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
In recent decades, the discourse on the relationship between religion and science has increasingly attracted the attention of scholars, particularly philosophers, scientists, and theologians. Religion and science are often perceived as distinct entities with roles and characteristics. This perspective has laid the groundwork for numerous studies exploring the interrelation between the two. This research aims to conduct a comparative analysis of arguments concerning religion and science from an Islamic perspective. The study uses a qualitative method through library research to draw upon various books and scholarly articles as its primary data sources. A historical and philosophical approach is adopted to examine the intersection of religion and science within Islamic intellectual thought. The data are analyzed using content analysis, involving critical interpretation of written materials, and supplemented by a comparative study of relevant arguments. The findings indicate that religion and science can coexist harmoniously without necessarily leading to conflict or contradiction. Throughout history, various efforts have been made to integrate these two domains, although some perspectives continue to emphasize their separation.